Translating and Interpreting in Intercultural Communication: A Study of Public Service Translators and Interpreters in Japan - Pratiwi, Putu Ayu Asty Senja (Universitas Nusantara PGRI Kediri, 2022)
The language and cultural barriers in the multilingual population have risen in Japan and resulted in the importance of public service translators and interpreters. Understanding thepublic service translators and interpreters’ roles and perspectives in intercultural communication in Japan is interesting and important to be investigated to explore the emotional and psychological impact on their work. Despite several research on translating, interpreting, or intercultural communication do exist, however the public service translators and interpreters’ emotional and psychological impact on their work has generally not been much researched. Therefore, it is necessary and meaningful to study the perspective and role of the public service translator and interpreters in the context of translation and intercultural communication.This research is based on the longitudinal observation and interview with ten public service translators and interpreters in Yamaguchi City, Japan. It was found that their preferences toward their work and other psychological aspects such as willingness to communicate, anxiety, and empathy also influence their role and perspective.